Ethical Problems of Transplantology - Ғуломова М.Қ., Худойбергенова П.Т. (Scholars Digest Publishing, 2023)
Transplantology is one of the most promising fields of medical science and practice, combining the latest achievements of modern surgery, resuscitation, anesthesiology, immunology, pharmacology and other medical and biological sciences, and relies on a set of advanced medical technologies. Transplantology's rise to the level of "physical" management of human death is not a specific, private medical issue, but rather a socio-cultural problem.
Keywords: Transplantology, surgery, reanimatology, anesthesiology, immunology, , reanimatology, anesthesiology, immunology.